Pelaksanaan K3 Proyek Pembangunan Rusun Mahata Serpong (Tinjauan Hukum) - Ifan Andriawan (CV Nature Creative Innovation, 2025)
This study examines the implementation of Occupational Safety and Health (OSH/K3) management in the construction project of Rusun Mahata Serpong, a large-scale transit-oriented development (TOD) residential complex in South Tangerang. As a vertical housing project initiated through inter-agency collaboration between the Ministry of Public Works and Housing (PUPR), the Ministry of Transportation, PT KAI, and the Ministry of State-Owned Enterprises, the construction process inherently carries significant occupational risks that require systematic OSH management. Using a qualitative case study approach, data were collected through field observation, interviews, and documentation involving ten workers who were directly engaged at the project site. The study evaluates key components of K3 management, including organizational structure, supervision mechanisms, communication flow, safety training routines, and the use of personal protective equipment (PPE). Findings indicate that the project has implemented an effective K3 organizational structure supported by routine safety briefings, adequate supervision, hazard identification procedures, and safety facilities such as protective barriers, warning boards, safety nets, controlled access gates, and evacuation routes. Daily PPE compliance is reinforced through direct reminders and visual safety signage. Based on interview results, eight out of ten respondents stated that K3 implementation at the project had been carried out according to company standards. Nonetheless, improvements are still recommended, particularly in strengthening supervision, enhancing workers’ safety awareness, and optimizing continuous K3 communication to build a stronger safety culture. Overall, the study highlights that consistent K3 implementation contributes significantly to ensuring worker protection and improving operational safety performance in high-risk construction environments.